Penggunaan Model Project Based Learning Dalam Meningkatkan Keterampilan Berbicara dan Menulis Teks Prosedur Pada Jenjang Sekolah Menengah Pertama (SMP) - Zahrah Delia Permana; Diena San Fauziya (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to describe the structure of procedural texts in the form of titles, objectives, tools/materials, and stages written by students at SMP. The method used is a descriptive method with a qualitative approach. The techniques used in this research are test, observation and questionnaire techniques. The data analysis techniques used are reading, grouping, speaking, presenting and concluding. By using the project based learning (PJBL) model by grouping students to improve speaking skills to realize the growth of motivation among students in their same group.